Employment Regulations through the Eyes of Employers : Do They Matter and How Do Firms Respond to Them? - Gaëlle Pierre; Stefano Scarpetta (Institute for the Study of Labor (IZA), 2004)
In this paper, we present evidence on how employers perceive labor regulations and react when these are perceived to constrain the operation of their firm. The paper draws from harmonized surveys of (up to) 17,000 firms around the world, and compares employers? responses with actual labor legislation. We find that employers? concerns about labor regulations are closely matched by the relative stringency of de jure labor laws. Countries that have, from an international perspective, tight labor regulations tend to have higher proportions of employers reporting these regulations as severe constraints. But not all firms are affected in the same way by onerous labor regulations. Medium sized firms are those whose business and prospect for growth are most negatively affected. Similarly, innovating firms are disproportionally affected by tight labor regulations. There is also clear evidence in the data that firms facing tight regulations invest more in training and make greater use of temporary employment. Small firms mainly rely on temporary employment, while medium and large firms, as well as innovating firms, tend to rely more on on-the-job training if labor regulations make hiring and firing very costly.
Keywords: K31; J23; J65; 330; employment protection indices; firms surveys; training; temporary employment; Arbeitsrecht; Personalbeschaffung; Betriebliche Weiterbildung; Befristeter Arbeitsvertrag